(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1991)
The stratigraphic succession of the Thakkhola region (central Nepal) begins in the Cambro-Ordovician with thick shallow-water carbonates, followed in the Siluro-Devonian by pelitic units deposited in deeper-water environments and at much higher accumulation rates with respect to the northwestern Himalaya sequence. During Carboniferous and Permian times, shallow-water limestones and coarse quartzose arenites were deposited, with major unconformities related to the initial opening of Neotethys. The following Triassic to Jurassic sedimentary units display comparable features all along the Tethys Himalaya. Owing to strong thermo-tectonic subsidence, the newly-formed Indian margin was rapidly drowned in the Early Triassic, and covered by thick marly limestones in Anisian to Carnian times. The Norian was characterized by very fine- grained quartzo-feldspathic detritus derived from the rejuvenated Indian foreland, while exclusive quartzose detritus suggests latitudinal drift towards more humid climates or more subdued relief in the Rhaetian. Shallow subtidal Early Jurassic limestones were covered in the Bajocian- Bathonian by bioclastic hybrid arenites, capped by a widespread condensed ironstone in the Early Callovian. In the Late Jurassic, black shales were deposited in outer shelf-slope conditions. The Cretaceous sedimentary evolution was related to the final fragmentation of Gondwanaland and initial opening of the Indian Ocean. Renewed quartzose detritus in the early? Neocomian was followed by deposition of thick deltaic to shallow-marine sandstones invariably characterized by abundant volcanic rock fragments. The northward-prograding deltaic complexes were overlain by a glauconitic condensed section, followed by late Albian pelagic marls. After the onset of collision berween India and Asia, the sedimentary units were involved in fold-thrust deformation at pre-anchimetamorphic to medium metamorphic grade, followed by uplift, formation of the Thakkhola graben and deposition of thick fluviolacustrine sediment in the Plio-Pleistocene.